The Asymmetry of Gender-Fluid Trends - Hoff, Maren; Bellezza, Silvia (Journal of Consumer Research, 2026)
Abstract Marketers and consumers are rapidly embracing gender-fluid products that fundamentally challenge the conventional associations of masculinity and femininity. In theory, manifestations of gender fluidity in the marketplace respond to shifting gender norms toward more inclusivity. Accordingly, consumers believe that the representation of traditionally male and female styles in these trends should be even. In contrast with these balanced views, this research demonstrates that gender-fluid trends to date skew toward traditionally male styles and that the corresponding adoption of gender-fluid products is driven relatively more by female and nonbinary consumers. Using a multimethod approach (including trend analyses of over 100,000 baby names, deep learning on a dataset of 200,000 products, and a series of experiments), this research defines gender fluidity in marketing; distinguishes it from related constructs such as gender-bending, unisex, and androgyny; and reveals a skewness in gender-fluid trends to date. It further demonstrates that women’s and nonbinary individuals’ heightened awareness of male advantages in society and lower fear of negative evaluation drive their greater adoption of gender-fluid styles.